Risk management for maize farmers in drought-prone areas of southern Africa. Procedings of a workshop held al kadoma ranch, Zimbawe, 1-3 oct. 1997 - International Maize and Wheat Improvement Center, México (México)International Crops Research Institute for the Semi-arid Tropics, Africa (Zimbawe (Africa), 1997)
Sumario (En)
Ilus., 109 ref.
Keywords: ZEA MAYS; AGRICULTORES; INVESTIGACION; MANEJO DEL SUELO; PRODUCTIVIDAD DE LA TIERRA; RIESGO; SISTEMAS DE EXPLOTACION; RIEGO; APLICACION DE ABONOS; POLITICA ECONOMICA; POLITICA DE DESARROLLO; AFRICA